Effect of aerated and non-aerated compost tea against some fungal phytopathogens: Effect of compost tea against fungal phytopathogens - Islam, Rinita; Sultana, Sabiha; Islam, Md. Rejaul; Mondal, Chhoa (Journal of the Bangladesh Agricultural University, 2019)
Suppressive effect of aerated and non-aerated compost tea against different fungal phytopathogens, namely Alternaria solani, Bipolaris sorokiniana, Fusarium oxysporum, Pestalotia palmarum and Sclerotium rolfsii was evaluated in Plant Protection Laboratory of Agrotechnology Discipline, Khulna University, Khulna, Bangladesh during 2016. Commercial compost, “Rastic Joibo Shar” was used to prepare aerated and non-aerated compost teas at 20% and 25% concentrations. All the treatments significantly inhibited the mycelial growth of tested five fungal phytopathogens. Among the five pathogens 25% concentration of non-aerated compost tea gave highest mycelial growth inhibition (76%) of Sclerotium rolfsii. Colony characteristics of five phytopathogens were significantly varied in all aspect by treating aerated and non-aerated compost teas at different concentrations. Finally it may be concluded that both aerated and non-aerated compost teas have suppressing effect on radial mycelial growth Thus compost tea may be used as alternatives to inorganic fertilizers/fungicides to suppress the pathogenic activity of the soil borne fungal phytopathogens. Thus based on the efficacy of in-vitro experiments, efficacy in field condition can be assessed against different diseases. J. Bangladesh Agril. Univ. 17(2): 142–147, June 2019